Applications of Electrochemistry and Nanotechnology in Biology and Medicine I - Eliaz, Noam.; SpringerLink (New York, NY Springer New York Imprint: Springer, 2011)
The study of electrochemical nanotechnology has emerged as researchers apply electrochemistry to nanoscience and nanotechnology. Containing recent breakthroughs, this is the first book of edited reviews of electrochemical applications in biology and medicine.
MONITORING OF CELLULAR DYNAMICS WITH ELECTROCHEMICAL DETECTION TECHNIQUES -- FUNDAMENTAL STUDIES OF LONG- AND SHORT-RANGE ELECTRON EXCHANGE MECHANISMS BETWEEN ELECTRODES AND PROTEINS -- MICROBIAL FUEL CELLS -- SCALABILITY AND THEIR USE IN ROBOTICS -- ELECTROCHEMICAL COATING OF MEDICAL IMPLANTS -- ELECTROCHEMICAL TECHNIQUES TO OBTAIN BIOFUNCTIONAL MATERIALS -- BIOACTIVE METALS PREPARED BY SURFACE MODIFICATION: PREPARATION AND PROPERTIES.
Electronic reproduction.
Keywords: Bioelectrochemistry; Nanomedicine; Electronic books